Decreased Programmed Death-1 Expression on the T Cells of Patients With Ankylosing Spondylitis. (June 2015) - Zhou, Lianlian; Zhang, Yanhong; Xu, Huiying; Hu, Liping; Zhang, Chunwu; Sun, Li; Xie, Yaosheng; Lu, Hong; Zhang, Zhuo; Hu, Wangqiang; Lin, Xiangyang
Abstract: Background: Programmed death-1 (PD-1) plays a vital role in down-modulating immune responses and maintaining peripheral tolerance. Methods: The authors have investigated the inducible expression of PD-1 on activated T cells from patients with ankylosing spondylitis (AS). Thirty patients with AS and 31 unrelated healthy controls (HCs) were recruited in this study. The expression of PD-1 on T cells harvested from nonstimulated (t0) or stimulated cultures with phytohemagglutinin for 24 hours (t24) was determined by flow cytometry. The multiple levels of the PD-1 expression on stimulated and nonstimulated cells from each individual's sample (t24/t0) represented as the degree of the inducible effect on PD-1 expression. Results: The expression of PD-1 on nonstimulated T cells presented no significant difference between AS group and HC group (P > 0.05). After stimulation, the degree of effect on PD-1 expression of CD4+, CD4+CD25+, CD4+CD25high, CD4+CD25low and CD4+CD25− T cells were significantly lower in patients with AS than those in HC group (1.9 ± 0.9 versus 3.6 ± 2.3, 9.7 ± 7.4 versus 17.8 ± 12.6, 87.8 ± 48.6 versus 157.3 ± 117.0, 3.7 ± 1.4 versus 7.3 ± 2.4, 0.5 ± 0.3 versus 1.1 ± 0.6, respectively, P < 0.05). However, there was no significant difference of the effect on all lymphocytes and CD8+ T cells between patients with AS and HCs (P > 0.05). Conclusions: The decreased inducible expression of PD-1 on active T lymphocytes, especially on CD4+CD25high and CD4+CD25+ T cells, may be one of important factors involved in the development of AS.